TONGA CASE STUDY Financing of NCD prevention in LMICs: Tonga Case Study - Ammar Rashid; Johanna Ralston; Kassim Nishtar; Saba Amjad (Journal of the Pakistan Medical Association, 2026)
Objective: To estimate spending on NCD prevention in Tonga and identify the enablers, challenges and dynamics underpinning population-level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organisational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorized into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government-routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: Tonga spent an estimated T 3.23 million (US 1.41 million) on NCD population prevention in 2018-19, constituting around 5.98% of total government health spending for the year. Donor spending constitutes a significant proportion of population-level NCD prevention spending. Enablers include increased tobacco taxes, inter-sectoral coordination, political leadership and use of the ‘settings’ approach. Challenges include rising levels of obesity, high costs of healthy diets and allocative and technical inefficiencies in fiscal and administrative systems. Conclusion: Tonga has made considerable progress in focusing policy attention and resources on NCD prevention and risk factors, at nearly 6% of government health spending. Increased population-level NCD prevention spending can help address the growing NCD burden and create economic benefits. “People used to eat papaya and tropical fruits, and walk to plantations but now they have western diet and go in a car even if it is 100 meters, children throw away the traditional diet and only have burgers” – Minister of Health, Tonga Keywords: Child, Noncommunicable Diseases, Tobacco, Behaviour, Automobiles, Clergy, Diet, Healthy, Fruit, Employees, Incidence, Leadership, Risk Factors Obesity, Taxes